Peningkatan Kapasitas Masyarakat dalam Penanggulangan Penyakit Degeneratif di Desa Ketapang Raya Kecamatan Keruak Kabupaten Lombok Timur - Bahri, Fathul; Prihartini, Sintia (Lembaga Publikasi Ilmiah Nusantara, 2024)
Degenerative diseases have become a significant health challenge in Indonesia, including in Ketapang Raya Village, Keruak Subdistrict, East Lombok Regency. These diseases, such as hypertension, diabetes mellitus, and heart disease, are often triggered by unhealthy lifestyle factors and a lack of public awareness regarding prevention and management. This study aims to examine efforts to enhance community capacity in addressing degenerative diseases in the village through a community empowerment approach. The research employs a participatory approach, involving the local community in various health education, training, and counseling activities. The programs implemented include increasing knowledge about healthy lifestyles, early disease detection, as well as stress management and balanced dietary habits. The results of the empowerment program indicate an improvement in the community's understanding of the risk factors for degenerative diseases, as well as a change in healthier behaviors, such as increased physical activity, improved dietary habits, and regular health monitoring. It is hoped that through this empowerment program, the community of Ketapang Raya Village will become more self-reliant in managing their health, reducing the prevalence of degenerative diseases, and improving the quality of life. This research contributes to the development of an effective community empowerment model in addressing health issues at the village level.